The Effect of Using Fintech On The Financial Behavior Of Teuku Umar University Students - Muzakir, Muzakir; Saputra, Agam (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2024)
This study aims to analyze how much Fintech influences the financial behavior of Teuku Umar University students.This is a quantitative study. The population in this study were all students and female students studying at Teuku Umar University, totaling 8,334 students. Determination of the sample using the Slovin formula, the sample obtained was 100 students at Teuku Umar University. The data collection technique is using a questionnaire. the analysis technique uses a simple regression test. The results showed that the use of fintech had a positive and significant effect on financial behavior.Keywords: Financial Technology, Financial Behavior